Efficient photodegradation of paracetamol by integrated PES-ZnO photocatalyst sheets - Chijioke-Okere, Maureen; Abdullah, Abdul Halim; Mohd Hir, Zul Adlan; Alinnor, Jude I.; Oguzie, Emeka E. (Elsevier, 2022)
In this study, PES-ZnO (Polyethersulphone-Zinc Oxide PZ) photocatalyst sheets were prepared via the phase inversion method and used in the oxidative degradation of paracetamol, a commonly detected pharmaceutical in water matrices. The incorporation of ZnO in the polymer matrix, confirmed by X-ray Diffraction (XRD), Scanning Electron Microscope/Energy Dispersive X-ray (SEM-EDX), and X-ray Photoelectron Spectroscopy (XPS) analyses, led to formation of porous structure with tear-like pores that subsequently increased the porosity of the polymer matrix PZ sheet. The PZ sheet containing 15 wt of ZnO, PZ-15, exhibited 92 degradation efficiency at a slightly alkaline condition when using four pieces of the PZ-15 sheet. The degradation rate constant of 4.8 — 10-3 minˆ’ 1 , based on pseudo-first-order kinetics, was obtained with hydroxyl radicals identified as the main species responsible for the degradation of paracetamol. The degradation process proceeded via hydroxyl radical attack of the C““C at the para position of the compound that yields hydroquinone as a by-product. The reusability study demonstrated the feasibility and reliability of using the PZ-15 photocatalyst sheet for up to six cycles with comparable performance in the degradation of paracetamol in an aqueous solution.